Peran motivasi dan kepemimpinan dalam meningkatkan kinerja karyawan di Departemen Quality Control PT Gokak Indonesia - Maryani, Maryani; Rahimi, Rahimi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study aims to explore the role of motivation and leadership in improving employee performance in the Quality Control Department of PT Gokak Indonesia. Employee performance is a key factor that influences product quality and company success. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving one supervisor and nine Quality Control employees. The findings indicate that intrinsic and extrinsic motivation significantly influence employees’ work spirit, satisfaction, and engagement. Intrinsic motivation, such as pride in work and self-development opportunities, encourages employees to be more accurate and productive. Extrinsic motivation, including recognition, compensation, and a supportive work environment, strengthens employee loyalty. Moreover, the participative leadership style of the supervisor plays an essential role in creating a positive work environment, enhancing collaboration, and fostering employees’ sense of belonging to the company. This study concludes that the synergy between motivation and effective leadership is crucial in improving employee performance, productivity, and product quality at PT Gokak Indonesia. The research provides theoretical contributions to human resource management literature and practical implications for developing motivation and leadership strategies in the textile industry.